Protective effect of aqueous extract of Adiantum capillus leaves against renal toxicity induced by gentamicin - Abdullah Ahmed, Measer; Mohammad Jasim, Jasim (Tikrit Journal of Pharmaceutical Sciences, 2023)
The study aimed to investigate the therapeutic effect of Aqueous Extract of Adiantum capillus-veneris leaves (AEA) against nephrotoxicity induced by Gentamicin. Twenty four adult male rats housed in animal house unit / college of veterinary, underwent to the necessary laboratory conditions. Study period was 8 days. Rats divided into four groups: first was normal control, second treated gentamicin(80mg/kg/day.im), third group treated with gentamicin(80mg/kg/day.im) and AEA(250mg/kg/day. oral) and fourth group treated with gentamicin (80mg/kg/day.im) and metformin (100mg/kg/day.oral). Blood were taken by cutting jugular vein serum were used to estimate levels of albumin, urea, creatinine, malondialdehyde(MDA), glutathione (GSH) and superoxide dismutase (SOD). Also Kidney were weighted and homogenate to estimate oxidant-antioxidant parameters. Results showed a significant increase in albumin, urea, creatinine, MDA and a significant decrease in GSH and SOD in rats treated by gentamicin compared to control in P<0.01, while treating by AEA and metformin showed a significant decrease in Albumine, Urea, creatinine, MDA and a significant increase in GSH and SOD and CAT in AEA group compared to gentamicin group. The significance was higher in AEA than metformin. We concluded that AEA has a therapeutic activity against nephrotoxicity induced by gentamicin in male rats.